2012
DOI: 10.1155/2012/320760
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reactions in a Complementary Medicine Hospital: A Prospective, Intensified Surveillance Study

Abstract: Background. Anthroposophic medicine is one of the widely used approaches of complementary and alternative medicine. However, few prospective studies have generated safety data on its use. Objectives. We aimed to assess adverse drug reactions (ADRs) caused by anthroposophical medicines (AMEDs) in the anthroposophical Community Hospital Havelhoehe, GERMANY. Study Design and Methods. Between May and November 2007, patients of six medical wards were prospectively assessed for ADRs. Suspected ADRs occurring during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
1
7
0
5
Order By: Relevance
“…25,35 Network data were also used to report ADRs for inpatients in the Community Hospital Havelhoehe. 36 The present study observed ADRs in relation to the number of drugs prescribed and patients exposed by physicians in a primary care network of CAM prescribers. Due to the method of collecting the complete prescription data, both CON and CAM treatments were analyzed for all patients over the complete study period; it was not possible to build groups of CAMversus CON-treated patients.…”
Section: ■■ Discussionmentioning
confidence: 73%
“…25,35 Network data were also used to report ADRs for inpatients in the Community Hospital Havelhoehe. 36 The present study observed ADRs in relation to the number of drugs prescribed and patients exposed by physicians in a primary care network of CAM prescribers. Due to the method of collecting the complete prescription data, both CON and CAM treatments were analyzed for all patients over the complete study period; it was not possible to build groups of CAMversus CON-treated patients.…”
Section: ■■ Discussionmentioning
confidence: 73%
“…Uma parte relativamente pequena dessas práticas e saberes -acupuntura, técnicas de meditação, plantas medicinais, entre outros -tem sido testada cientificamente, mas com estudos inconclusivos, devido às evidências escassas sobre sua eficácia 1,4,9,10,11,12 . Há também estudos que avaliam as reações adversas e, portanto, a segurança no seu uso (principalmente de plantas medicinais e suplementos alimentares) e que concluem pela necessidade de maior aprofundamento no tema 1,11,12 .…”
unclassified
“…Há também estudos que avaliam as reações adversas e, portanto, a segurança no seu uso (principalmente de plantas medicinais e suplementos alimentares) e que concluem pela necessidade de maior aprofundamento no tema 1,11,12 . Tal validação científica é específica para alguns problemas ou doenças, conforme as teorias e a nosografia biomédicas, e impõe limites na avaliação desses saberes e prá-ticas 10,12,13 . No geral, isola-se técnicas terapêuti-cas para doenças ou situações específicas, com métodos que satisfazem ou se aproximam de padrões instituídos pela biomedicina 12,13,14,15,16 .…”
unclassified
See 2 more Smart Citations